2013
DOI: 10.1007/s13238-013-3009-x
|View full text |Cite
|
Sign up to set email alerts
|

Structures of SdrD from Staphylococcus aureus reveal the molecular mechanism of how the cell surface receptors recognize their ligands

Abstract: Staphylococcus aureus is the most important

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…Molecular modeling revealed that the B repeats pack in a zig-zag fashion, suggesting that they could effectively provide the needed orientation and stability to present the A region away from the bacterial cell surface (9). For the S. aureus SdrD protein, which also contains the CnaB-like fold (36), it has been proposed that the B repeats could function as a spacer and a spring, helping to expose the adhesin (36). Our observations differ from the conclusions of an earlier study on purified proteins, suggesting that the structure, function, and folding of the ligand-binding A region are not affected by the presence of the B region and thus that the latter does not influence collagen binding (7).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular modeling revealed that the B repeats pack in a zig-zag fashion, suggesting that they could effectively provide the needed orientation and stability to present the A region away from the bacterial cell surface (9). For the S. aureus SdrD protein, which also contains the CnaB-like fold (36), it has been proposed that the B repeats could function as a spacer and a spring, helping to expose the adhesin (36). Our observations differ from the conclusions of an earlier study on purified proteins, suggesting that the structure, function, and folding of the ligand-binding A region are not affected by the presence of the B region and thus that the latter does not influence collagen binding (7).…”
Section: Discussionmentioning
confidence: 99%
“…The overall domain organization of Bbp/SdrE is similar to that of ClfA, except that there are three B repeats inserted between the A domain and SD repeat region (Josefsson et al, 1998a). These B repeats, which bind Ca 2+ , each adopt a β-sandwich fold and are thought to act as a spring-like linker connecting the A domain to the SD repeats (Josefsson et al, 1998b; Wang et al, 2013). Although Bbp was originally identified as a bone sialoprotein binding protein (Tung et al, 2000), it was later found to bind fibrinogen with high affinity (Vazquez et al, 2011).…”
Section: Fibrinogen/fibrin Mediated Clumpingmentioning
confidence: 99%
“…All three chains have been shown to be critical for pathogenic adherence (Cheung et al 1991;Otto 2013). The crystal structure of several fibrinogen-binding MSCRAMMs have been solved so far, including ClfA (PDB ID 1N67) (Deivanayagam et al 2002), ClfB-Fg peptide complex (PDB ID 4F20) (Xiang et al 2012), SdrD (PDB ID 4JDZ) (Wang et al 2013a) from S. aureus, Srr-1 (PDB ID 4MBO) and Srr-2 (PDB ID 4MBR) (Seo et al 2013) from S. agalactiae, and SdrG (PDB ID 1R19 and 1R17, native and complex with fibrinopeptide, respectively) from Staphylococcus epidermidis (Ponnuraj et al 2003). When superposed, they share a highly conserved structural homology, but exhibit much less sequence identity (<20%) than that observed in collagen-binding MSCRAMMs.…”
Section: Fibrinogen-binding Mscrammsmentioning
confidence: 99%
“…Concerning the B-repetitive region in fibrinogenbinding MSCRAMMs, the crystal structure is available only for one B-repeat region of SdrD of S. aureus (Wang et al 2013a). This structure also contains the ligand-binding A-region (N2 and N3 domains), which precedes the B-repeat.…”
Section: Fibrinogen-binding Mscrammsmentioning
confidence: 99%